SISTEM INFORMASI MONITORING SALES (STUDI KASUS PADA PT. PENERBIT ERLANGGA MAHAMERU CABANG SEMARANG) (Information Technology and Telematics, 2015)
Abstract- PT. Penerbit Erlangga Mahameru Cabang Semarang will always monitor the performance of the sales book sales. Monitoring process can be seen from the number of  books sold each day , so that the results of such monitoring can generate a sales report sales every day. The process of monitoring the sale of sales at PT. Penerbit Erlangga Mahameru Cabang Semarang is less effective and takes a long time. Objectives to be achieved is to create a system of monitoring sales information on PT. Penerbit Erlangga Mahameru Cabang Semarang can monitor daily sales performance and easy in making sales report . The results in this study is the monitoring system sales PT. Penerbit Erlangga Mahameru Cabang Semarang  for this is still less effective and takes a long time. With the new monitoring system can monitor the performance of the sales of  books by sales PT. Penerbit Erlangga Mahameru Cabang Semarang and can present sales reports , report book entry , monitoring reports with fast , accurate , precise and easy that can facilitate admin. Keywords - Monitoring, Sales, PT. Penerbit Erlangga Mahameru Cabang Semarang